"Carryover phenomenon" in subcutaneous implantable cardioverter‐defibrillator: Residual energy caused early shock to subsequent ventricular tachycardia. Issue 3 (5th April 2022) - Yamagishi, Yasunobu; Oginosawa, Yasushi; Yagyu, Keishiro; Miyamoto, Taro; Keita, Tsukahara
Abstract : We reported a case of early S‐ICD shock due to the carryover of previously charged energy. Depending on the interval with the preceding event, an early shock may occur for the subsequent event. Especially, in cases where non‐sustained VTs occur frequently, the indication for S‐ICD surgery should be considered carefully.